Santarém, entre la Amazonia de los ríos y la Amazonia de las carreteras - Rubén Valbuena (Confins)
The great northern area of Brazil, Amazonia, which during several centuries represented only an enormous vacuum and a source of potential richness, has been during the last half-century the object of an accelerated process of occupation and of intensive exploitation. A strong dynamics of appropriation facilitated the incursion of new human and financial resources into the Amazonian hinterland, especially during three last decades, when the realization of a ground network articulated the right bank of the big river.This network restructured the regional space, until then dominated by the rivers and a weak network of populated places, formed by small settlements at the edge of the inland waterways. Santarém, a historical city with a strategic localization between the two greater Amazonian urban centres, has been the theatre of enormous transformations since the construction of the road. The connection, via the Cuibá-Santarém road, with the Center-West region of Brazil and, via Transamazonian road, with the Brazilian North-East and Western Amazonia, started to play a significant role as articulator of the Northern area. At the same time, it became the principal focus of settlement of this vast central area, by organizing an emergent process of regional construction.